Soil-feeding termites build islands of soil physical and chemical fertility in pastures in Colombian Amazon. - Ervin Humprey Duran-Bautista; Adriana M Silva-Olaya; María P Llanos-Cabrera; Katherin Yalanda-Sepúlveda; Juan Carlos Suárez (PLoS ONE)
Soil-feeding termite species, such as Patawatermes turricola (Silvestri, 1901), construct mounds that significantly alter soil properties; this species is an abundant mound-builder in the Amazon region. This study evaluated physicochemical changes in termite mounds and in Urochloa decumbens (Stapf) R. Webster pastures with scattered trees and rotational grazing at the Centro de Investigaciones Amazónicas Macagual - César Augusto Estrada González in the northwestern Colombian Amazon. This region receives approximately 3793 mm of annual rainfall and is characterized by Ultisol soils, which are acidic, cation-poor, and clay-dominated, where the termite P. turricola is predominant. The study hypothesized that mound-building activities by soil-feeding termites improve the soil physical and chemical properties by creating island of soil fertility. To test this hypothesis, we collected soil samples from the outer mound wall and unmodified topsoil 5 m away to determine porosity, bulk density, aggregate stability, aggregate-size distribution, cations, organic carbon, available phosphorus, and exchangeable acidity, these physicochemical characteristics were selected due to their potential impact on soil fertility and ecosystem function. Our results showed that termites significantly improved soil aggregate stability, as reflected in a higher weighted mean diameter value in the mound (3.88 mm) than in unmodified topsoil (3.57 mm). Macro-porosity was also higher in the mound (18.49% vs. 11.47%). Higher content of soil cations, available phosphorus, and organic C  was also detected in soil mound than unmodified topsoil, as well as higher soil organic carbon (27.1 g kg-1 vs. 23.3 g kg-1). In contrast, exchangeable acidity was higher in surrounding soil. The mound soil presented a positive impact on soil fertility and structure compared to the adjacent topsoil. The findings obtained support the hypothesis that the mound-building activity of P. turricola termites significantly improves the physical and chemical properties of the soil by creating islands of fertility in nutrient-poor agroecosystems.